2017
DOI: 10.4172/2090-4568.1000174
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intermittent Limiting Anodic Current Stimulation on the Electro Activity of Anodic Biofilms

Abstract: Journal of Advanced Chemical EngineeringZhang et al., J Adv Chem Eng 2017, 7:1 DOI: 10.4172/2090 Volume AbstractElectro active biofilms is key components of bio electrochemical systems. Anodic biofilms formed by a potentialadaptive way (i.e., operation with constant external resistance or poised anode potentials) generally lack the ability to adapt to limiting currents. In the present study, a strategy based on intermittent limiting anodic current application was first employed to directly stimulate the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Higher current densities have been reported when electro-active bacteria are grown under intermittent anode potential regimes [ 9 , 10 ] compared to continuous potential. Until now, studies have focused on the EAB adaptation to this intermittent anode potential regime aiming at linking biofilm composition and morphology to bioanode performance (current, charge recovered and Coulombic efficiency) [ 11 , 12 ]. It has been observed that the biofilm morphology on the electrode changes to a more porous structure when an intermittent potential regime is applied [ 10 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Higher current densities have been reported when electro-active bacteria are grown under intermittent anode potential regimes [ 9 , 10 ] compared to continuous potential. Until now, studies have focused on the EAB adaptation to this intermittent anode potential regime aiming at linking biofilm composition and morphology to bioanode performance (current, charge recovered and Coulombic efficiency) [ 11 , 12 ]. It has been observed that the biofilm morphology on the electrode changes to a more porous structure when an intermittent potential regime is applied [ 10 , 13 ].…”
Section: Introductionmentioning
confidence: 99%